The Effects of Syntactic Awareness to L2 Chinese Passage-Level Reading Comprehension - Zhou, Jing (Frontiers in Psychology, 2022)
This study aimed to investigate the association between syntactic awareness and L2 Chinese passage-level reading comprehension in 209 Chinese as a second language adult-learners. The participants were administered a character knowledge test, vocabulary knowledge test, morphological awareness test, a grammatical judgement and correction test, a word order test, and two types of reading comprehension tests (multiple-choice questions test and cloze test). Partial correlation analyses showed that the participants’ performance in two syntactic awareness tasks were significantly positively correlated with their passage-level reading comprehension. Multiple regression analyses showed indicated that syntactic awareness made a unique contribution to L2 Chinese reading even when age, major, gender, length of learning Chinese, character knowledge, vocabulary knowledge, and morphological awareness were controlled for. Findings also suggested that the contribution of two syntactic awareness tasks was associated with how L2 passage level reading comprehension was measured.